POT IKLAN BERTENAGA SURYA - Kiki Prawiroredjo; Citra Laras (Website, 2013)
Abstract The Solar Powered Display Vase is a vase designed to display an outdoor advertisement. The circuit applies sun light energy as the power supply to save energy and environment friendly. The advertisement is displayed by Light Emitting Diodes (LED) as a simulation. An accumullator is used as the power supply and it will be charged automatically by a sel surya. A microcontroller is used to control the process of the circuit. After the circuit is constructed and tested, it is known that if the output voltage of the solar cell is above 1.8V the LEDs are off and they are on if the voltage is less than 1.8V. Keywords: LED, Microcontroller, sel surya.